2022
DOI: 10.2147/dddt.s371596
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Nalbuphine in Surgical Patients Undergoing General Anesthesia with Varying Degrees of Liver Dysfunction

Abstract: This study aimed to characterize the pharmacokinetics of nalbuphine in patients undergoing general anesthesia with varying degrees of liver dysfunction. Patients and Methods: Twenty-four patients were enrolled and divided into three cohorts based on liver function: normal liver function (n = 13), mild liver dysfunction (n = 5), and moderate/severe liver dysfunction (n = 6). During the induction of anesthesia, they received 15 mg of nalbuphine intravenously. Venous blood samples were collected from each patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…The typical values of nalbuphine PK parameters from the final model were 32.9 L/h for CL, 32.5 L for V1, 245 L/h for Q and 83.5 L for V2. The results were consistent with our previous results, which were obtained using non-compartmental analysis (NCA) ( Gao et al, 2022 ). While Bressolle et al (2011) built a PopPK model of nalbuphine after surgery in children (1–11 years) using an allometric scaling model, and their population parameter estimates were 130 L/h/70 kg for CL, 210 L/70 kgforV1, 75.6 L/70 kg for Q and 151 L/70 kg for V2.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The typical values of nalbuphine PK parameters from the final model were 32.9 L/h for CL, 32.5 L for V1, 245 L/h for Q and 83.5 L for V2. The results were consistent with our previous results, which were obtained using non-compartmental analysis (NCA) ( Gao et al, 2022 ). While Bressolle et al (2011) built a PopPK model of nalbuphine after surgery in children (1–11 years) using an allometric scaling model, and their population parameter estimates were 130 L/h/70 kg for CL, 210 L/70 kgforV1, 75.6 L/70 kg for Q and 151 L/70 kg for V2.…”
Section: Discussionsupporting
confidence: 93%
“… Sear et al (1987) found that nalbuphine exhibited lower total clearance (CL) and apparent volume of distribution (V d ) in anesthetized patients compared with the results obtained in awake volunteers. Similarly, our previous study ( Gao et al, 2022 ) found that nalbuphine CL(33.42 L/h) and V d (137.69 L) were significantly lower in patients undergoing general anesthesia than in healthy patients (CL 90.0 L/h; V d 326.5 L) ( He et al, 2021 ), regardless of whether the patient had liver dysfunction. However, neither of these studies analyzed the reasons for the above-mentioned results.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations